2019
DOI: 10.2478/pneum-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary rehabilitation and tuberculosis: a new approach for an old disease

Abstract: Tuberculosis (TB) is still a leading cause of morbidity and mortality worldwide. The impact on patient’s life is significant, leading to physical, mental and social deconditioning, not only in active TB but also in post TB sequela. Although with specific antituberculous treatment sputum negativity can be achieved, TB extrapulmonary symptoms such as cachexia, muscle weakness and depression may persist for a long time. The pulmonary rehabilitation (PR) may be a useful tool in this patient’s therapy in active and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…6 Pulmonary rehabilitation has also been proven to improve symptomatology, degree of functional independence, quality of life, and independence of TB patients in performing ADL. 7 Improvement in lung condition is the first development that can be observed in these two cases. With improved ventilation, oxygen supply to the brain is increased.…”
Section: Discussionmentioning
confidence: 85%
“…6 Pulmonary rehabilitation has also been proven to improve symptomatology, degree of functional independence, quality of life, and independence of TB patients in performing ADL. 7 Improvement in lung condition is the first development that can be observed in these two cases. With improved ventilation, oxygen supply to the brain is increased.…”
Section: Discussionmentioning
confidence: 85%
“…Early case-finding, treatment initiation and treatment completion, resulting in interruption of TB transmission, reduction of mortality and addressing possible co-morbidities, through dedicated and multidisciplinary outreach services are key to eliminate TB among social risk groups in Romania, and indirectly reduce TB incidence among the general population, as well as tackling blood-borne virus diseases among the risk groups. 22 …”
Section: Discussionmentioning
confidence: 99%
“…In Ukraine, the results of a study showed that PR should be applied at all disease stages, starting at the stationary phase and continuing during the outpatient and homecare phases. A recommendation of this study was that the session's exercise duration should be no more than 30 minutes 3-5 times a week for 8-12 weeks [49].…”
Section: Frequency and Duration Of The Programmentioning
confidence: 99%